Endogenous protective mechanisms in remodeling of rat heart mitochondrial membranes in the acute phase of streptozotocin-induced diabetes - Ferko, Miroslav; Kincelová, Dana; Waczulíková, Iveta; Mujkošová, Jana; Kucharská, Jarmila; Šikurová, Libuša; Ziegelhöffer-Mihalovičová, Barbara; Styk, Ján; Ziegelhöffer, Atila (Physiological research, 2008)
The aim of present study was to investigate functional and physical alterations in membranes of heart mitochondria that are associated with remodeling of these organelles in acute phase of streptozotocin-induced diabetes and to elucidate the role of these changes in adaptation of the heart to acute streptozotocin-induced diabetes (evaluated 8 days after single dose streptozotocin application to male Wistar rats). Action of free radicals on the respiratory chain of diabetic-heart mitochondria was manifested by 17 % increase (p<0.05) in oxidized form of the coenzyme Q(10) and resulted in a decrease of states S3 and S4 respiration, the respiratory control index, rate of phosphorylation (all p<0.01) and the mitochondrial transmembrane potential (p<0.05), but the ADP/O ratio decreased only moderately (p>0.05). On the contrary, membrane fluidity and the total mitochondrial Mg2+-ATPase activity increased (both p<0.05). In diabetic heart mitochondria, linear regression analysis revealed a reciprocal relationship between the increase in membrane fluidity and decrease in trans-membrane potential (p<0.05, r = 0.67). Changes in membrane fluidity, transmembrane potential, Mg2+-ATPase activity and the almost preserved ADP/O ratio appear as the manifestation of endogenous protective mechanisms participating in the functional remodeling of mitochondria which contributes to adaptation of the heart to diabetes.
Keywords: Animals; experimentální diabetes mellitus; ubichinon; srdeční mitochondrie; Ca(2+) Mg(2+)-ATPase; Rats, Wistar; Membrane Potential, Mitochondrial; Mitochondria, Heart; Free Radicals; Ca(2+)-Mg(2+)-ATPasa; Oxidative Phosphorylation; fyziologická adaptace; mitochondriální membrány; fluidita membrány; transport elektronů; Membrane Fluidity; Ubiquinone; oxidativní fosforylace; Male; membránový potenciál mitochondrií; Adaptation, Physiological; krysa rodu Rattus; Mitochondrial Membranes; zvířata; mužské pohlaví; Myocardium; myokard; Rats; volné radikály; Electron Transport; potkani Wistar; Diabetes Mellitus, Experimental